Инновационный контейнер для транспортировки и хранения отработавшего ядерного топлива - Vasilyev A. S., Bogdanov D. M. (Science, education, society: tendencies and future development, 2017)
in an innovative container for transportation and storage of spent nuclear fuel cast cover is fixedly connected to the body of ductile cast iron with nodular graphite due to the shrinkage that occurs during solidification of the melt of ductile iron with nodular graphite in the manufacture of body casting.
Keywords: отработавшее ядерное топливо; хранение; высокопрочный чугун; ductile iron; транспортно-упаковочный комплект; transport and packaging; spent nuclear fuel storage